A Rhetorical Analysis of the Covid-19 Pandemic Process: Turkish Minister of Health Dr. Fahrettin Koca’s Press Briefings - Sema Çağlayan (Connectist Istanbul University Journal of Communication Sciences)
This study sought to reveal discourse characteristics in speeches made by the Minister of Health, Fahrettin Koca, pertaining to Covid-19 rather than ideological or political matters. Koca has been the most prominent actor in managing the risk and fear caused by Covid-19. The speeches in question were delivered after Scientific Committee meetings during the period from 11 March 2020, when the first case of Covid-19 appeared in Turkey, to May 11, 2020, when controls on social life were first applied. A total of 15 press statements were analyzed and were divided into individual sentences to obtain 1,801 individual pieces of data. The data were examined using qualitative and quantitative content analysis in the context of the “Five Canons of Rhetoric” and Aristotle’s “Three Modes of Persuasion.” They were then coded into SPSS for analysis, which allowed frequency (N) and cross tabulations (CrossTabs) to be calculated. Analysis based on Aristotle’s three modes of persuasion demonstrated that logos was the most prominent persuasion component. The apparent goal of convincing the public with justifications and evidence rooted in logos reflects the need to engender trust during the pandemic crisis and to control the spread of panic. Analysis based on the five canons of rhetoric showed that speeches were structured with clear sections. Narrative sections and explanations were included predominantly to provide sufficient information to contextualize the topics under discussion, and the use of sub-components of persuasion was tailored to the context of the subject in each relevant section. A preference for plain and short sentences was also identified, but ornamentation was also present and the speaker used body language effectively. Considering that the speeches addressed all of Turkey and frequently included medical explanations, they were clearly structured carefully. The use of plain language was likely designed to reduce potential semantic accidents, while elements of ornamentation helped to sustain public interest and to enliven the discourse. These findings indicate that rhetorical elements are widely present in press statements.